Exploring the rights of nature in freshwater and marine ecosystems - Rhomir S. Yanquiling; Gabriela Cuadrado-Quesada; Susanne Schmeier (Earth System Governance)
Recognizing nature as a legal subject could be understood as an innovative way to transform environmental law towards an ethos of respect and care. The Rights of Nature (RoN) movement gained traction at a time when planet Earth is facing unprecedented ecological degradation. So far, little attention has been given as to how RoN is interpreted and conceptualised and what its implications are to freshwater and marine ecosystem governance. Moreover, important questions remain insufficiently answered, including, for instance, the question of who grants such rights and on the basis of which legal mechanisms, who legally represents nature, or how such rights are actually being implemented and possibly enforced. This article explores the different legal conceptualizations of RoN, focusing on freshwater and marine ecosystems which have received particular attention in recent years in both the academic discourse and in policy practice – yet remain under immense pressure. It also investigates which legal mechanisms are being used to recognize these rights – e.g. court cases, laws, ordinances– and what their legal implications have been so far, including the challenges which have to be addressed to ensure that this innovative approach indeed helps transform how societies perceive and govern freshwater and marine ecosystems.